Feto-maternal Outcomes in Patients of Oligohydramnios: A Prospective Observational Study - Anturlikar, Snehal S; Desai, Haresh A (Journal of Neonatal Surgery, 2025)
Background: Oligohydramnios referred to as decreased amniotic fluid index (AFI) <5 cm [1] is a serious disorder affecting 4.4% of pregnancies [2]. Borderline oligohydramnios, i.e. AFI between 5.1 to 8 cm also can lead to unwanted outcomes in pregnancy. Less than normal amount of amniotic fluid may lead to complications like restricted growth, underdeveloped organs, fetal distress, less birth weight, preterm birth, prolonged labor, uteroplacental insufficiency, etc. [3] L-arginine, a semi-essential amino acid is suggested to improve amniotic fluid index. [2] Hence our study was planned to know effect of L-arginine in oligohydramnios patients at our centre. Materials and Methods: This was a prospective observational study undertaken in a tertiary care teaching hospital which included 200 patients diagnosed with oligohydramnios from 1st January 2023 to 31st October 2024. Institutional ethics committee permission (PUIECHR/PIMSR/00/081734/5306) was obtained before data collection. All pregnant women with singleton pregnancies diagnosed with oligohydramnios and satisfying inclusion criteria were included and data was recorded for those who received L-arginine along with those who came directly for delivery without receiving L-arginine. Results: Out of 200 patients diagnosed with oligohydramnios, 100 patients received L-arginine and 100 patients came directly for delivery and did not receive L-arginine. Of those receiving L-arginine, the average gestational age of starting L-arginine therapy was 35.3 ± 2.1 weeks while gestational age at delivery was 37.4 ± 1.82. Hence, there was an increase of 2.1 ± 0.27 weeks of gestational age at an average. The increase in AFI after treatment with L-arginine was 0 to 3 cm with a mean of 0.735 cm. Conclusion: Our study showed a significant increase in gestational age as well as an increase in AFI with the administration of L-arginine. For establishing beneficial role of L-arginine in oligohydramnios, more such studies with bigger sample size are needed.